Medical radionuclide production science and technology - Qaim, S. M. (Syed M.) 1941- (De Gruyter, 2020)
The work describes the production technology of standard medical radionuclides using reactors and cyclotrons for patient diagnosis and therapy. A special focus lies on the science and technology involved in the development of novel radionuclides for positron emission tomography (PET) and internal targeted radiotherapy. The availability of those radionuclides is opening up new potential in clinical research, especially in neurology, cardiology and oncology. The future perspectives of the developing technology are also discussed. -- Provided by publisher